2018
DOI: 10.1002/cam4.1395
|View full text |Cite
|
Sign up to set email alerts
|

Risk of thyroid cancer in relation to height, weight, and body mass index in Japanese individuals: a population‐based cohort study

Abstract: Greater height and body mass index (BMI) have been associated with an increased risk of thyroid cancer incidence in Western countries. However, few epidemiological studies have assessed the association between anthropometric factors, such as BMI, height, or weight, and thyroid cancer incidence in Asian populations. Using the population‐based Japan Public Health Center‐based prospective study database, we investigated the relationship between anthropometric factors and thyroid cancer incidence. Data on anthropo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Increased BMI is also associated with increased risk of thyroid cancer [26] and 44.1% of WTCHP responders reported a BMI 25–29 km/m 2 , with an additional 44.1% reporting a BMI >30 km/m 2 . Neta et al reported 15.9% and 12% of the thyroid cancer cases having a BMI of 25–29, and ≥30 km/m 2 , respectively, which is lower than what was observed in the WTCHP cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Increased BMI is also associated with increased risk of thyroid cancer [26] and 44.1% of WTCHP responders reported a BMI 25–29 km/m 2 , with an additional 44.1% reporting a BMI >30 km/m 2 . Neta et al reported 15.9% and 12% of the thyroid cancer cases having a BMI of 25–29, and ≥30 km/m 2 , respectively, which is lower than what was observed in the WTCHP cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analysis (55) makes clear that thyroid cancer risk is positively associated with BMI in women. Studies that have assessed this in older or post-menopausal women in particular are generally consistent with a modest in increase in risk (56)(57)(58)(59)(60)(61)(62). Case-control (63) and cohort analyses (58,(64)(65)(66) have not reported clear associations with unopposed menopausal estrogen therapy.…”
Section: Cancer Of the Thyroidmentioning
confidence: 97%
“…Several studies have examined the relationship between obesity (measured by body mass index [BMI]) and thyroid cancer risk. Most (4)(5)(6)(7)(8)(9), but not all (10,11), suggest that obesity is associated with increased thyroid cancer risk in both women and men. However, it is possible that the observed association does not reflect a biological relationship between obesity and thyroid cancer but instead could reflect more frequent use of health care services by people who are overweight or obese (12,13), with consequent increased opportunity for ascertainment of indolent thyroid lesions.…”
Section: Introductionmentioning
confidence: 99%